Proposing a virtual operations network to support a business policy for the medicinal and aromatic plants sector - Almeida, I.; Silva, J. (Proceedings of the 18th Cambridge International Manufacturing Symposium, 2014)
This research found out a more robust conceptual basis behind three missing links concerning the requirement for a virtual operations network to support a business policy for the Medicinal and Aromatic Plants (MAP) sector. Industry was pictured from secondary data gathered from a 12 experts panel. The factors to configure a collaborative network, e.g. relationships and structure, enabled the operationalisation of a previously defined social platform. Requirements for information infrastructure, co-ordination and DSS were also expressed. Moreover, the role of enterprise knowledge to the formation of collaborative ventures helped the modelling of the social-momentum of the platform. Finally, it is argued (i) for the confirmation of a significant Operations Management contribution to defining a MAP policy and, (ii) for the outlining of a collaborative network representing an advance to the usually ambiguous prescriptions of virtual operations. An interview guide to run an empirical test could be generated as further work.